Seeing Is Believing: Miracles, Providence, and Reality in the Talmuds - Rozen-Tsevi, Yishai (Toronto journal of theology, 2017)
The last chapter of tractate Berakhot ("Benedictions") is exceptional. It does not discuss the set daily liturgy, as does the rest of the tractate, but rather presents benedictions to be said following encounters with various phenomena, both seen and heard. These benedictions carry none of the permanence of the fixed liturgy, but are reflexive to the world around them. This makes the closing chapter a rare depository of information about the rabbinic world view. In this list of phenomena and their appropriate liturgical responses, the discerning reader can detect the manner in which the rabbis theologically conceptualize the world around them. This article focuses on the benediction that opens the chapter—for miracles—and the discussions about it in the two Talmuds. A close reading of these discussions reveals some of the ways in which rabbis in Roman Palestine and Sassanian Babylonia explained miracles and account for their (non)existence in their own reality.